Infrastructure Bonds as a Funding Tool for Attracting Financial Resources for Financing Railway Modernization Projects within the Framework of PPP in Ukraine - A. Yermolenko, O; Ðž. Kokovikhina, O; Ð† Boiko, D; M. Lysonkova, N (International Journal of Engineering and Technology, 2018)
The article concerns the analysis of the funding sources for modernization projects at OJSC Ukrzaliznytsia (UZ). Moreover, it has been proved that the self-financing enterprises of UZ in the process of expanded creation are inefficient. It is noted that infrastructure bonds within the framework of public-private partnership (PPP) may become a new promising form of financing infrastructure projects in Ukraine. The analysis of the international practice made it possible to identify some of the features functioning infrastructure bonds and its specifics for the railway industry. It has been established that advantages of this type of securities cause increased interest to them from the stock market participants, both nonprofessional and portfolio investors, which include insurance companies, investment funds and pension funds. It is proposed to the issuance of infrastructure bonds with the rate of return "average deposits rate of Ukrainian banks plus 3%". Such a rate of return in the conditions of existence of state guarantees would interest to potential investors. The purpose of the article is to reveal the content and features of the use of infrastructure bonds in financing public-private partnership projects in the railway industry and to substantiate the practical recommendations for their application.Â Â